Sensitivity to the Average and Summative Impact of Multiple Events: When "More is More" and When "More is Less". Issue 1 (March 2020) - Seta, John J.; Seta, Catherine E.
How people respond to positive and negative events is a basic question in psychology. Most theoretical accounts assume that the detrimental impact of negative life events is cumulative, resulting in a "more is more" effect. A similar assumption of "more is more" is typically used to predict the influence of multiple positive life events, people's reactions to evaluative stimuli (e.g., an audience), and their judgments of consumer goods. In this article, we present a model that suggests that these conclusions do not capture the full picture of how people respond to multiple positive or negative events. More specifically, the averaging/summation (A/S) model does not predict that the underpinnings of individuals' responses to positive or negative events always reflect summative affective impact. Rather, individuals' responses often reflect the average value of events, as well as their summative value. We review research supporting the model's predictions and discuss alternative theories and interpretations, such as the conservation of resource model, the peak–end rule, mental accounting, distraction, and assimilation/contrast. In addition, we suggest new avenues for research.